Laços afetivos na UTI: a visita que fala de uma identificação - SILVA, Aline Tavares Machado (2017)
This study aimed to investigate what motivates someone affectively to attend the ICU (Intensive Care Unit) patient visit of a public hospital. Therefore, it used a search in the literature to review the literature on studies that addressed disease process and health, affect, and research in documentary sources, legal provisions and other normative frameworks related to public health, which Includes the Humanization Policy, which came to regulate the presence of an interdisciplinary team in hospitals, which allowed and legitimized the place of psychologists in various sectors of medical specialties, including the ICU. The studies included a qualitative analysis of these concepts, with the aim of portraying a little of the reality of the visitors who clashed with the universe of the Intensive Care Unit and, consequently, directly or indirectly, with the imminence of death Of someone you know.